The acceptance model for camera simulators as a learning media for Indonesian vocational student - Suwastika, Novian Anggis; Masrom, Maslin; Qonita, Qori; Yasirandi, Rahmat; Nuha, Hilal Hudan (Institute of Advanced Engineering and Science, 2024)
This study investigates the acceptance of camera simulator technology as a learning media by Indonesian vocational high school (VHS) students and examines the relationships among influencing factors. It proposes an acceptance model integrating the technology acceptance model (TAM) 3 and the unified theory of acceptance and use of technology (UTAUT). Ten factors impacting technology acceptance were identified, resulting in the formulation of 15 hypotheses regarding inter-construct relationships. In this empirical study, a quantitative approach was employed, distributing questionnaires to 200 students at Public Vocational High School 10 in Bandung, specializing in broadcasting and filmmaking programs. After analyzing 145 valid responses, the study progressed in two stages: the measurement model and the structural model. The evaluation of the measurement model confirmed the validity of all indicators and constructs, ensuring compliance with the established standards. In the structural model evaluation, one construct (computer anxiety) and four inter-construct relationships were excluded. This research enhances our understanding of factors influencing camera simulator technology acceptance among VHS students in Indonesia, shedding light on the complexities of their decision-making process in adopting this educational tool.